Emergency care utilization by refugee children compared to controls: A statewide database analysis - Anna H. Abrams; Jan Leonard; Sarah E. Brewer; Janine Young; Kathleen M. Adelgais (PLoS ONE, 2025)
Background Refugees face barriers to accessing healthcare despite provision of short-term services after arrival. Limited access to sustained primary care may lead to increased emergency department (ED) utilization and little is known regarding how refugee children access emergency care. Objective To compare the proportion of ED claims and median level of service (LOS) between refugee children and general population controls in a statewide claims database. Methods We conducted a retrospective cohort study of medical claims for patients aged 0 to 18 years old in a statewide claims database from 2014–2019. Refugee claims were identified using deterministic linkage of children with known refugee status. Procedure and diagnosis ICD9/10, Healthcare Common Procedure Coding System, and Current Procedural Terminology codes were obtained from the statewide database to indicate type of claim (ED vs outpatient) and LOS. Demographics were extracted from a data warehouse. Primary outcome was the number of ED claims per 1000 combined ED and outpatient claims. LOS was measured as a proxy for ED visit complexity. We compared demographics, frequency of claims, and median LOS using chi-square. Results There were 5,590,808 total claims with 1,235,476 ED claims. Median number of ED claims per individual patient was the same between groups, however the proportion of claims related to an ED visit was significantly higher in the refugee population than the general population controls (244 vs 221, p = 0.001). Median LOS for ED claims was Level 3 (99283) and there was no difference between groups. Conclusion Proportion of ED claims was higher in a refugee population compared to controls with no differences in LOS, indicating higher ED utilization among refugees for all acuity levels. Further study is needed to determine if healthcare disparities account for this difference and if population specific services may support the care of the refugee children.